Gibson's paradox, monetary policy, and the emergence of cycles - Greg Hannsgen (Levy Economics Institute of Bard College, 2004)
Many empirical studies have found that interest rate have a positive effect on the price level. This paper pursues an obvious, but neglected explanation: interest payments are a cost of production that is at least in part passed on to costumers. A model shows that the cost-push effect of inflation, long known as Gibson's paradox, intensifies destabilizing forces and can be involved in the generation of cycles. An empirical investigation finds that the positive association of interest rates with inflation or the log of the price level is present in data from the 1950s to present.
Keywords: C22; E11; E12; E32; E52; 330; Gibson's Paradox; Inflation; Monetary Policy Rules; Nonlinear Dynamics